Demand forecasting and order planning in supply chains and humanitarian logistics - Taghipour, Atour, 1974- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book focuses on demand anticipation, forecasting, and order planning as well as humanitarian logistics to propose original solutions for existing problems"--